(untitled) (Czech Journal of International Relations, 2002)
Petr Drulák /ed./: National and European Identitites in EU Enlargement. Views from Central and Eastern Europe. 1st ed. Prague: Institute of International Relations, 2001, 224 stran, ISBN 80-86506-11-8.